Endophytic Fungi—Alternative Sources of Cytotoxic Compounds: A Review - Uzma, Fazilath; Mohan, Chakrabhavi D.; Hashem, Abeer; Konappa, Narasimha M.; Rangappa, Shobith; Kamath, Praveen V.; Singh, Bhim P.; Mudili, Venkataramana; Gupta, Vijai K.; Siddaiah, Chandra N.; Chowdappa, Srinivas; Alqarawi, Abdulaziz A.; et al. (Frontiers in Pharmacology, 2018)
Cancer is a major cause of death worldwide, with an increasing number of cases being reported annually. The elevated rate of mortality necessitates a global challenge to explore newer sources of anticancer drugs. Current advances in cancer treatment involve the development of novel and improved chemotherapeutics derived from natural or synthetic sources. Natural sources offer the potential of finding new structural classes with unique bioactivities for cancer therapy. Endophytic fungi represent a rich source of bioactive metabolites that can be manipulated to produce desirable novel analogues for chemotherapy. This review offers a current and integrative account of clinically used anticancer drugs such as taxol, podophyllotoxin, camptothecin and vinca alkaloids in terms of their mechanism of action, isolation, characterization of the bioactive compound, yield obtained and strain improvement strategies. It also covers recent literature on endophytic fungal metabolites from terrestrial, mangrove and marine sources as potential anticancer agents and emphasizes the findings for cytotoxic bioactive compounds tested against specific cancer cell lines.